This Is Not a Pipe - Foucault, Michel (Berkeley, Los Angeles, London : University of California Press, 1983)
What does it mean to write This is not a pipe across a bluntly literal painting of a pipe. René Magritte's famous canvas provides the starting point for a delightful homage by the French philosopher-historian Michel Foucault. Much better known for his incisive and mordant explorations of power and social exclusion. Foucault here assumes a more playful stance. By exploring the nuances and ambiguities of Magritte's visual critique of language, he finds the painter less removed than previously thought from the pioneers of modern abstraction - confronting them and within a common system, a figure at once opposed and complementary. Foucault's brief but extraordinarily rich essay offers a startling, highly provocative view of a painter whose influence and popularity continue to grow unchecked. This Is Not a Pipe also throws a new, piquantly dancing light on Foucault himself. In the French philosophe Michel Foucault, himself no mean practitioner of the oddball, Magritte's looking glass pipe has found its Lewis Carroll. This essay not only proposes a new understanding of Magritte, it also constitutes a perfect illustration and introduction to the thought of the philosopher himself, France's great wizard of paradox. Magritte's respectful fan letters to Mr. Foucault, which are included in this volume, the useful introduction and splendid translation by James Harkness and the handy ... black and white reproductions of many of Magritte's works combine to make this a document of extraordinary interest.
Engels
boek
Keywords: Magritte, René